Fracture resistance of cantilevered full-arch implant-supported hybrid prostheses with carbon fiber frameworks after thermal cycling. (January 2022) - Haroyan-Darbinyan, Evelina; Romeo-Rubio, Marta; Río-Highsmith, Jaime Del; Lynch, Christopher D.; Castillo-Oyagüe, Raquel
Abstract: Objectives: This in vitro study aimed to find the best combination of mesostructure and veneering materials for full-arch implant-supported hybrid prostheses (HPs) in terms of the fracture resistance (FR) of their cantilevers. Methods: Three groups ( n  = 5 each) of maxillary HPs were fabricated: Group-1 (CC-A, control ): Co-Cr frameworks coated with acrylic resin; Group-2 (CF-A): carbon fiber veneered with acrylic resin; and Group-3 (CF-R): carbon fiber coated with composite resin. All specimens were submitted to 5, 000 thermal cycles (5 °C – 55 °C, dwell time: 30 s), and subjected to a single cantilever bending test in a universal testing machine (crosshead speed: 0.5 mm/min) until failure. The fracture pattern was assessed using stereo microscope and SEM. The one-way ANOVA and Bonferroni tests were run ( α = 0.05). Results: The FR yielded significant differences among the three groups ( p < 0.001). CC-A samples reached the highest FR values ( p  ≤ 0.001), whereas both CF-A and CF-R HPs exhibited the comparably ( p  = 0.107) lowest FR. CC-A specimens failed cohesively (100%): mostly without chipping (80%). CF-A mesostructures were always broken at the connections of the distal implants. CF-R prostheses often failed adhesively (80%). Conclusions: The HPs made of Co-Cr veneered with acrylic demonstrated the best mechanical behavior, being the only group whose 13-mm long cantilevers exceeded the clinically acceptable FR of 900 N. The HPs constructed with carbon fiber frameworks showed, additionally, more unfavorable fracture patterns. Clinical significance: For HPs with cantilevers up to 13 mm, Co-Cr mesostructures coated with acrylic may represent the optimum combination of materials.